2020
DOI: 10.1183/13993003.02651-2020
|View full text |Cite
|
Sign up to set email alerts
|

The interrelatedness of chronic cough and chronic pain

Abstract: BackgroundSince chronic cough has common neurobiological mechanisms and pathophysiology with chronic pain, both clinical disorders might be interrelated. Hence, we examined the association between chronic cough and chronic pain in adult subjects in the Rotterdam Study, a large prospective population-based cohort study.MethodsUsing a standardised questionnaire, chronic pain was defined as pain lasting up to 6 months and grouped into a frequency of weekly/monthly or daily pain. Chronic cough was described as dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Chronic cough is more prevalent in females than males, with studies reporting 66-73% of patients to be female [27,30]. This mirrors similar findings for chronic pain, and comorbid daily chronic pain and chronic cough, which are also more prevalent in women than in men [31], possibly due to shared neural pathways. Data from a functional magnetic resonance imaging study, involving inhalation of subtussive concentrations of capsaicin, suggest these gender prevalence effects may reflect differences in central neural processing of the cough sensation [27].…”
Section: Epidemiologysupporting
confidence: 53%
“…Chronic cough is more prevalent in females than males, with studies reporting 66-73% of patients to be female [27,30]. This mirrors similar findings for chronic pain, and comorbid daily chronic pain and chronic cough, which are also more prevalent in women than in men [31], possibly due to shared neural pathways. Data from a functional magnetic resonance imaging study, involving inhalation of subtussive concentrations of capsaicin, suggest these gender prevalence effects may reflect differences in central neural processing of the cough sensation [27].…”
Section: Epidemiologysupporting
confidence: 53%
“…Consequently, our findings may not be generalizable to hospital-based cohorts. Fifth, chronic pain might be a major confounding factor in the chronic cough-depression link [40]. However, because we did not have chronic pain data during this study period in the Rotterdam Study, we could not adjust for it in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding chronic cough at a population level can also provide a different perspective and may identify other associated risk factors, for example, occupational exposure to dust/fumes 16 and chronic pain 39 . This study showed many other cardio-vascular and mental health conditions that were associated with a higher incidence of chronic cough in a population.…”
Section: Discussionmentioning
confidence: 99%